Assessing radiation protection practices among radiological workers - Fathi A. Awushah; Rajab.B. Yousef; Maryem M. Alswehly (Surman Journal of Science and Technology, 2025)
Radiologic technologists represent a special group at the forefront of occupational radiation exposure. In Libyan hospitals and diagnostic centers, it is observed that radiologic technologists who deal with ionizing radiation on daily basis, show non-compliance to international safety standards of radiation protection regarding use of improperly shielded equipment. The current study aimed to assess awareness of radiation protection, its implementation and health-related outcomes among radiologic technologists working in various hospitals. A self‑administered 12‑item questionnaire was distributed to a cohort of 68 radiologic technologists working in Zawia, Sorman, Sabratha, Trauma Aboslim, Tripoli Central and Tripoli Medical Central Hospitals over the period from July 2022 until August 2022. The schematic questionnaire included sections on department layout, presence of protective devices, individual practice of protection and personal protective practices, instruction issues, monitoring of employees' health and record keeping. There were low compliance rates with radiation protection standards, use of dosimeters (15%) and training (26%). At a departmental level, major design problems were noted by 64% of respondents and only half (52%) reported that protective equipment was widely available. The study demonstrates significant gaps for radiation protection infrastructure, monitoring and training, among Libyan R.Ts. This underscores the urgent need for regulation, proper training and enforcement of protective measures.